Building a Sustainable Circular Agri-Food Supply Chain For Rural Producer Organization - Andika, Alif; Perdana, Tomy; Chaerani, Diah; Utami, Hesty Nurul (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
The development of a sustainable circular agri-food supply chain for rural producer organizations is essential to address the challenges of food loss, agricultural waste management, and resource efficiency. This study explores the integration of circular economy principles within the vegetable supply chain of rural producer organization, emphasizing the utilization of waste as a resource through technologies. Using a mixed-methods approach, the research analyzes the current state of waste management practices, quantifies losses across production and post-harvest stages, and identifies opportunities for improvement. The findings highlight significant inefficiencies in waste utilization, revealing that daily losses result in financial losses amounting to 4-10% of potential revenue. A sustainable circular supply chain model is employed to analyze and coordinate the interdependencies and decision-making processes among stakeholders, ensuring efficient resource allocation, effective waste management, and the integration of circular economy principles to achieve sustainability outcomes. By aligning production processes with circular economy principles, rural producer organizations can reduce environmental impacts, improve economic resilience, and contribute to the long-term sustainability of the agri-food supply chain.